2020
DOI: 10.1101/2020.05.04.076638
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tumor-specific changes in Kaposi sarcoma-associated herpesvirus genomes in Ugandan adults with Kaposi sarcoma

Abstract: Intra-host evolved tumor virus variants have provided insights into the risk, pathogenesis and treatment responses of associated cancers. However, the intra-host variability of Kaposi sarcoma-associated herpesvirus (KSHV), the etiologic agent of Kaposi sarcoma (KS), has not been explored at the whole viral genome level. An accurate and detailed description of KSHV intra-host diversity in whole KSHV genomes from matching tumors and oral swabs from Ugandan adults with HIV-associated KS was obtained by deep, shor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 120 publications
(128 reference statements)
0
1
0
Order By: Relevance
“…Yet sequence variation did not correlate with disease risk (344). A Ugandan study of KSHV genomes from tumors and oral swabs found that genomes were identical at the point mutation level within individuals but intra-host tumor-associated KSHV mutations and genome sequences impacting protein coding were present (345). On the host side, an association likely exists between HLA polymorphisms and susceptibility to KSHV infection and related diseases (346).…”
Section: Transmission Risk Factors Malignancies Control Strategiesmentioning
confidence: 99%
“…Yet sequence variation did not correlate with disease risk (344). A Ugandan study of KSHV genomes from tumors and oral swabs found that genomes were identical at the point mutation level within individuals but intra-host tumor-associated KSHV mutations and genome sequences impacting protein coding were present (345). On the host side, an association likely exists between HLA polymorphisms and susceptibility to KSHV infection and related diseases (346).…”
Section: Transmission Risk Factors Malignancies Control Strategiesmentioning
confidence: 99%